ANTIBACTERIAL AND ANTIFUNGAL ACTIVITY OF CRUCIFEROUS VEGETABLES - CAULIFLOWER, BROCCOLI - S, SUNDAR; A, JAYARAMI REDDY (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: This work aims to analyze the antibacterial and antifungal activities of cruciferous vegetables such as cauliflower and broccoli. Methods: Cruciferous vegetables act as a good source of natural antioxidants due to their high levels of carotenoids, tocopherols, and ascorbic acid. In this study, two cruciferous vegetables, such as cauliflower and broccoli, were selected for antibacterial and anti-fungal studies. The stems, flowers of cauliflower, and broccoli were extracted with 125 mL of ethanol and water by Soxhlet’s apparatus for 6 h. Mueller Hinton agar and Sabouraud’s dextrose agar medium were used for antibacterial and antifungal activity, respectively. The antibacterial and antifungal activities of each cauliflower, broccoli stem, and flower extract were determined using a modified Kirby–Bauer disk diffusion method. Standard antibiotics, gentamicin (25 μg/mL), and fluconazole (25 μg/mL) served as positive controls for antibacterial and antifungal activity, respectively. Results: Broccoli stem (100 μg/mL) ethanol extract produced higher antibacterial activity (13 mm) against Escherichia coli. Cauliflower, flower (100 μg/mL) ethanol extract produced higher antibacterial activity (13 mm) against Staphylococcus aureus. Broccoli flower (100 μg/mL) ethanol extract produced higher antifungal activity (14 mm) against Candida albicans. According to the results obtained from this project, broccoli stems and flower ethanol extracts show very good antibacterial activity against Gram-negative microorganisms such as E. coli and Pseudomonas aeruginosa. Similarly, cauliflower, flower ethanol extract shows excellent antibacterial activity against Gram-positive microorganisms such as Bacillus subtilis and S. aureus. Conclusion: Further analysis is recommended for the identification of active constituents responsible for these activities.